Urban mobility and organization of public transport in Tizi Ouzou, What diagnostic and what prospects? - LOUANI , Kahina; KEBICHE , Abdelhakim (Journal of Human Sciences, 2020)
This article is based on the idea of "better knowing, to better plan", based on the notion of urban-transport interaction, through the study of the practice of mobility, and the presentation of the results of the household travel survey, carry out in 2016 among household in the city of T.O, in order to evaluate the characteristics of their mobility. The objective is to evaluate the characteristics of their journeys, and to analyse the quality of supply and demand for urban transport, and finally the prospects for this sector.